Statement of accounts Bangladesh Rural Advancement Committee for the year ended 31st December, 1986 - BRAC (© BRAC, 2016)
This Financial Statement prepared by M. Ahmed & Co. Chartered Accountants, 67, Bangabandhu avenue, Dhaka-2.